Implementasi Perluasan Makna Asas Legalitas Berdasarkan Kitab Undang-Undang Hukum Pidana (KUHP) Nasional - Anggia Nur Ramadhani. D; Maya Shafira; Erna Dewi; Gunawan Jatmiko; Damanhuri Warganegara (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2024)
Purpose: The purpose of this study is to determine how to expand the meaning of the principle based on the National Criminal Code. Methodology: The method used was a normative juridical approach and an empirical juridical approach with a qualitative research type. Primary and secondary data sources were used. Results: The results of the research show that the laws that exist in society to obtain a form of legal certainty based on the provisions of Pasal 2 Ayat (3) of the National Criminal Code are required to compile the customary laws that exist in each region concerned to be selected and then included in the regulations. Area. This is a form of implementing the expansion of the meaning of the principle of legality into Regional Regulations. Limitations: This study is only related to expanding the meaning of the principle of legality in the National Criminal Code. Contribution: This research is expected to be a reference and contribute to the application of expanding the meaning of the principle of legality in reality.